Measurement of Organizational Commitment in Private Hospitals in Chennai City - Libia, Palayan (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
Organisational commitment is considered to be a positive psychological sate which binds an employee to the organisation. Several research studies have established that highly commitment employees remain with the company .organisation commitment found to be inversely related to employees in private hospitals in Chennai city. This study investigated the relationship between organisation effective, organisation culture and organization commitment. In this research correlation analysis was carried out to describe the link between the employee’s commitment and organisation commitment.